2021
DOI: 10.1038/s41467-020-20100-8
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 neurons in the parabrachial nucleus mediate taste perception

Abstract: The neural circuitry mediating taste has been mapped out from the periphery to the cortex, but genetic identity of taste-responsive neurons has remained elusive. Here, we describe a population of neurons in the gustatory region of the parabrachial nucleus that express the transcription factor Satb2 and project to taste-associated regions, including the gustatory thalamus and insular cortex. Using calcium imaging in awake, freely licking mice, we show that Satb2 neurons respond to the five basic taste modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
2
41
1
Order By: Relevance
“…TRPV1-lineage positive gustatory neurons frequented the lateral PB nucleus including its external subregion (Figure 1H). Other studies have described gustatory activity in lateral PB areas including the external capsule (Yamamoto et al, 1994;Geran and Travers, 2009;Tokita et al, 2014;Tokita and Boughter, 2016;Jarvie et al, 2021), with the present and our prior work (Li and Lemon, 2019) identifying trigeminal projections reach taste cells in this PB region.…”
Section: Chr2 Expression In the Trigeminal Tract Was Regulated By Cre In Trpv1-lineage Fiberssupporting
confidence: 72%
“…TRPV1-lineage positive gustatory neurons frequented the lateral PB nucleus including its external subregion (Figure 1H). Other studies have described gustatory activity in lateral PB areas including the external capsule (Yamamoto et al, 1994;Geran and Travers, 2009;Tokita et al, 2014;Tokita and Boughter, 2016;Jarvie et al, 2021), with the present and our prior work (Li and Lemon, 2019) identifying trigeminal projections reach taste cells in this PB region.…”
Section: Chr2 Expression In the Trigeminal Tract Was Regulated By Cre In Trpv1-lineage Fiberssupporting
confidence: 72%
“…First, the transcription factor Satb2 marks PB neurons that relay gustatory information to the thalamus (Fu et al., 2019; Huang et al., 2013; Jarvie et al., 2021; Maeda et al., 2009). We confirmed that both Satb2 mRNA (not shown) and Satb2 immunofluorescence (Figure 18a) identify a restricted distribution of PB neurons, primarily at caudal levels.…”
Section: Resultsmentioning
confidence: 99%
“…Most injection sites and implants were larger than most PB subpopulations, which intermingle extensively, so these approaches simultaneously targeted subsets of PB neurons with distinct connections and functions. Now, genetic methods allow investigators to target more specific subpopulations, including an overlapping potpourri of neurons that express Satb2, Calca , Pdyn, Cck , Oxtr1 , Htr2c , Oprm1 , or Tacr1 (Barik et al., 2021; Chiang et al., 2020; Fu et al., 2019; Garfield et al., 2014; Jarvie et al., 2021; Kaur et al., 2017; Liu et al., 2021; Norris et al., 2021; Palmiter, 2018; Park et al., 2020; Ryan et al., 2017; Yang et al., 2020). Limiting the immense potential of this approach were the lack of a framework for understanding ontological relationships between subpopulations and a lack of markers for remaining PB neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Miniscope imaging also revealed that bidirectional modulation within genetically defined cell types is responsible for the varied permutations of consumptive decision-making, as glutamatergic neurons in the median preoptic area (MPOA) bidirectionally respond to water intake [ 42 ] and clusters of glutamatergic neurons in the anterior peri-locus coeruleus are activated or inhibited by food and water intake [ 43 ]. Single-cell recordings of parabrachial neurons expressing transcription factor Satb2 have also shown that the same neurons can be excited or inhibited by different taste stimuli [ 44 ]. Importantly, some miniscope results have challenged earlier findings on hunger and thirst that originated from studies lacking single-cell resolution.…”
Section: Scientific Applications In Rodent Modelsmentioning
confidence: 99%